Physiological quality of soybean seeds produced in four edaphoclimatic regions of Santa Catarina - Frandoloso,Volmir (2015)
Abstract:The production of soybeans in the state of Santa Catarina is quite significant in the national context, since the state is recognized for producing seeds with high standards of physiological quality, due to the use of modern technologies and favorable climatic conditions. The aim of this study was to evaluate the physiological quality of soybean seeds produced by major companies in the state of Santa Catarina, analyzed in three seasons: harvesting (reception at UBS), after processing and at the time of sale. The experiment was conducted in the state of Santa Catarina, in the main regions and companies producing commercial soybean seeds: Xanxerê (companies A, B and C), Abelardo Luz (companies D and E), and Campus Novos (companies F and G), in addition to Canoinhas, which was evaluated with a single producer (company H). Data analysis and interpretation of the results showed that the soybean seeds produced in different regions have adequate quality for sowing and germination within the standards required for marketing, except the BRS 295 cultivars and Don Mario 7.0i company "F".